The Palestinian Diaspora: Status and Rights in Middle East and North African Countries - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2024)
The Palestinian diaspora, beginning with a mass exodus following the establishment of Israel in 1948, has faced diverse and evolving challenges in Middle Eastern and North African host countries. This paper explores the historical and contemporary status of Palestinian refugees in these regions, examining the legal, social, and economic conditions they endure. While neighboring Arab states initially supported Palestinian refugees, their experiences have since been defined by prolonged refugee status and fluctuating levels of hostility. In Lebanon, Jordan, Syria, Egypt, and the Gulf countries, policies have fluctuated based on geopolitical interests and local dynamics. North African countries, while offering some support, also reflect the complexities of Palestinian integration. The ongoing refugee crisis underscores the need for international efforts to address the root causes and ensure the rights and welfare of Palestinian refugees.